2021
DOI: 10.24191/jeeir.v9i2.12739
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intention to use reusable drinking straw

Abstract: Single-use plastic drinking straws is difficult to recycle and is one of the main causes of water pollution and marine animal destruction. An option for single use drinking straws is reusable ones. This study applies the theory of planned behavior (TPB) to determine the factors affecting the intention to use reusable drinking straw using a survey method in Selangor, Malaysia. Based on an OLS multiple regression result, the study concluded that attitude and perceived behavioral control are significant predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…It is a process wherein the beliefs of a reference group or, more specifically, significant persons, such as family, friends, and the PLOS ONE community, affect an individual's observations, opinions, and feelings [34]. The strong influence of subjective norms on pro-environmental intention has been shown in preceding studies [73,80,81]. Soomro et al [64] studied psychological factors influencing solid waste recycling intentions.…”
Section: H1: Attitude Positively Affects Consumers' E-waste Recycling...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a process wherein the beliefs of a reference group or, more specifically, significant persons, such as family, friends, and the PLOS ONE community, affect an individual's observations, opinions, and feelings [34]. The strong influence of subjective norms on pro-environmental intention has been shown in preceding studies [73,80,81]. Soomro et al [64] studied psychological factors influencing solid waste recycling intentions.…”
Section: H1: Attitude Positively Affects Consumers' E-waste Recycling...mentioning
confidence: 99%
“…According to Hirsh et al [ 99 ], people with high levels of neuroticism are more concerned about negative consequences, and their environmental distress makes them afraid of the ecological damage that waste can cause. Numerous recent studies have found that neuroticism has a role in pro-environmental behavior [ 39 , 73 , 80 ]. Neuroticism influences pro-environmental behavior in a positive and significant way [ 88 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies have focused on systematic interventions to promote reusable drink cups [ 3 , 10 , 25 ]. Many studies have been conducted to understand reusable drink cups or bottles [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies have proven that a positive attitude is an essential antecedent of behavioral intention, such as in the recycling and reuse of plastic wastes [ 5 ], e-waste disposal behavior [ 45 ], recycling of solid waste [ 46 ], the purchase of energy-efficient appliances [ 41 ], mobile waste recycling [ 42 ], and suboptimal foods [ 43 ]. Specifically, studies revealed that attitude has a positive influence on the intention to reuse drink cups and straws [ 3 , 10 , 25 ]. Based on previous studies, we can assume that attitude is an essential antecedent of university students’ intention to use reusable drink cups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation